Investigation on the ballistic performance of the aluminum matrix composite armor with ceramic balls reinforcement under high velocity impact - Ali Ansari; Tayebeh Akbari; Masoomeh Rahimi Pishbijari (Defence Technology, 2023)
In this research, the ballistic behavior of the ceramic-reinforced aluminum matrix composite plates is investigated to provide an optimal design for protecting against 7.62 mm bullet at the speed of 800 m/s experimentally and numerically. The target materials are Al5083 alloy as the metal matrix and alumina ceramic balls as the reinforcement. To simulate a 3D numerical model, ABAQUS FE code has been utilized. After validation the numerical model by experiments, the effect of ceramic ball weight percentage include 15%, 30% and 45% and the target thickness 20, 25 and 30 mm is considered on the ballistic results like the kinetic energy, residual velocity and depth of penetration. Finally, it was found that the specimen with 25 mm thickness and 30% alumina is optimum based on existing ballistic protection criteria.